Integration of CO2 absorption with biological transformation via using rich ammonia solution as a nutrient source for microalgae cultivation. (15th July 2019) - Song, Chunfeng; Xie, Meilian; Qiu, Yiting; Liu, Qingling; Sun, Luchang; Wang, Kailiang; Kansha, Yasuki
Abstract: Energy penalty of solvent regeneration in CO2 absorption process is a critical challenge. To avoid the energy consumption, novel ammonia absorption-microalgae hybrid CO2 capture process has been designed in this work. In the proposed process, the conventional desorption column is replaced by a microalgae cultivation system. As a result, the NH4 HCO3 could be utilized as nutrient for microalgae growth and converted into biofuel or value-added ingredients. Meanwhile, the challenge of ammonia escape could be avoided via high purity ammonia recycling in the hybrid process. The experimental results indicated that the selected Chlorella sp. L166, L38 and UTEX1602 could be potential microalgae to be used in chemical-biological hybrid CO2 capture and utilization process with carbon fixation efficiency over 85%, and the yield of protein, lipid and polysaccharides was 164 ± 1 mg/L (L166), 710.6 ± 165.8 mg/L (UTEX1602) and 143.6 ± 28.8 mg/L (L38), respectively. The above results also indicated that the novel absorption-microalgae hybrid process could be a promising alternative to the conventional CO2 absorption technology. Highlights: Novel absorption-microalgae hybrid CO2 capture and utilization process was put forward. NH4 HCO3 in the rich ammonia solution was converted into value-added ingredients via microalgae. Energy-intensive regeneration treatment was avoided in the hybrid process. Escaped ammonia in the hybrid process could be recycled for subsequent CO2 absorption.